Research approaches to the investigation of the issue of the Roma ethnic group - Vasić Aleksandar D.; Srdić Vesna M. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2014)
Dealing with many and various problems presented by the reality of the Roma ethnic group is at the centre of interest of numerous scientific disciplines and social sciences. Compiling the inventory of new and fresh items of knowledge about various aspects of the Roma life is an important element of a wider field of research in which the Roma are one of the ethnic groups under scientific investigation. Readiness to treat the Roma in the spirit of humanist tradition which in modern times has been accepted as a paradigm of human development, has launched numerous initiatives by society and social institutions to realize a justified request that the problems of the position of the Roma deserve to be treated in the context of both science as well as the global context of social structure. The research into essential questions of the life of the Roman community comprise a number of historical, ethnological, anthropological, demographic and sociological aspect which can be investigated together can be placed within a scientific framework.